Effect of processing on the mechanical properties of insulating epoxy - Nur Hidayah Ramlan (Nanyang Technological University, 2022)
Effect of processing on the mechanical properties of cured epoxy resins has been studied. During the preparation process of an epoxy material, one of the most common induced defects that occurs are voids. The presence of these voids strongly influence the mechanical properties of the cured epoxy resins and one of the solutions to tackle this issue is effective degassing process. The cured epoxy resin samples in this study were prepared with a standard mixing time of 1 minute and varied degassing time ranging from 0 to 30 seconds. Dynamic mechanical properties, such as storage modulus (E'), loss modulus (E''), damping (tan δ) and glass transition temperature (Tg), and mechanical properties such as tensile strength and thermal characteristics were evaluated. Fractured surfaces were observed using field emission scanning electron microscopy. In general, the experimental results suggest that the sample with the longest degassing time exhibited superior mechanical, dynamic mechanical and thermal properties.